Collagen‐binding proteins of Streptococcus mutans and related streptococci. (25th April 2016) - Avilés‐Reyes, A.; Miller, J.H.; Lemos, J.A.; Abranches, J.
Summary: The ability of Streptococcus mutans to interact with collagen through the expression of collagen‐binding proteins (CBPs) bestows this oral pathogen with an alternative to the sucrose‐dependent mechanism of colonization classically attributed to caries development. Based on the abundance and distribution of collagen throughout the human body, stringent adherence to this molecule grants S. mutans with the opportunity to establish infection at different host sites. Surface proteins, such as SpaP, WapA, Cnm and Cbm, have been shown to bind collagen in vitro, and it has been suggested that these molecules play a role in colonization of oral and extra‐oral tissues. However, robust collagen binding is not achieved by all strains of S. mutans, particularly those that lack Cnm or Cbm. These observations merit careful dissection of the contribution from these different CBPs towards tissue colonization and virulence. In this review, we will discuss the current understanding of mechanisms used by S. mutans and related streptococci to colonize collagenous tissues, and the possible contribution of CBPs to infections in different sites of the host.